The handbook of financing growth : strategies, capital structure, and M & A transactions - Marks, Kenneth H. (Wiley finance series., 2009)
Kenneth H. Marks, Larry E. Robbins, Gonzalo Fernndez, John P. Funkhouser, and D.L. Williams. Praise for The handbook of Financing Growth. "Once again, Kenneth Marks and company have hit the mark with a comprehensive analysis of corporate and commercial finance, which is both readable and up-to-date. This book is a must for any entrepreneur, middle-market company CFO, or graduate student looking for a thorough presentation of real world financial solutions. I highly recommend it."